2014
DOI: 10.1121/1.4898426
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of ablative ability of high-intensity focused ultrasound cavitation-based histotripsy on mechanical properties of agar

Abstract: Cavitation-based histotripsy uses high-intensity focused ultrasound at low duty factor to create bubble clouds inside tissue to liquefy a region, and provides better fidelity to planned lesion coordinates and the ability to perform real-time monitoring. The goal of this study was to identify the most important mechanical properties for predicting lesion dimensions, among these three: Young's modulus, bending strength, and fracture toughness. Lesions were generated inside tissue-mimicking agar, and correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…In preliminary experiments conducted without the top fibrin layer, the vast majority of cells were detached within in a single pulse, including cells farther away from the bubbles. This observation makes sense based on previous work showing that histotripsy is dependent upon tissue mechanical properties (Xu and Bigelow 2011;Vlaisavljevich et al 2014a;Vlaisavljevich et al 2014b;Xu et al 2014;Vlaisavljevich et al 2015a;Vlaisavljevich et al 2015b), which are determined by the extracellular matrix, intracellular matrix, and cellmatrix adhesions. During the multi-pulse experiments, cells at the bubble cloud boundary were deformed numerous times and often bisected multiple times before complete removal.…”
Section: Discussionmentioning
confidence: 94%
“…In preliminary experiments conducted without the top fibrin layer, the vast majority of cells were detached within in a single pulse, including cells farther away from the bubbles. This observation makes sense based on previous work showing that histotripsy is dependent upon tissue mechanical properties (Xu and Bigelow 2011;Vlaisavljevich et al 2014a;Vlaisavljevich et al 2014b;Xu et al 2014;Vlaisavljevich et al 2015a;Vlaisavljevich et al 2015b), which are determined by the extracellular matrix, intracellular matrix, and cellmatrix adhesions. During the multi-pulse experiments, cells at the bubble cloud boundary were deformed numerous times and often bisected multiple times before complete removal.…”
Section: Discussionmentioning
confidence: 94%
“…In preliminary experiments conducted without the top fibrin layer, the vast majority of cells were detached within in a single pulse, including cells farther away from the bubbles. This observation makes sense based on previous work showing that histotripsy is dependent upon tissue mechanical properties (Xu and Bigelow 2011; Vlaisavljevich et al 2014a; Vlaisavljevich et al 2014b; Xu et al 2014; Vlaisavljevich et al 2015a; Vlaisavljevich et al 2015b), which are determined by the extracellular matrix, intracellular matrix, and cell-matrix adhesions. During the multi-pulse experiments, cells at the bubble cloud boundary were deformed numerous times and often bisected multiple times before complete removal.…”
Section: Discussionmentioning
confidence: 95%
“…Since previous work has demonstrated that tissue mechanical properties significantly impact histotripsy (Xu and Bigelow 2011; Vlaisavljevich et al 2014a; Vlaisavljevich et al 2014b; Xu et al 2014; Vlaisavljevich et al 2015a; Vlaisavljevich et al 2015b), an optically transparent fibrin-based tissue phantom with an embedded layer of human breast cancer cells (BCCs, MDAMB231) was used to mimic adherent cells inside a tissue-like ECM environment. Cell culture work was performed under ThermoForma Class II A1 Biological Safety Cabinet and cells were incubated at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The degassed agar/n-propanol solution was combined with the heated evaporated milk, poured into a mold, and allowed to solidify at 5° C. This formation has previously been shown to replicate the density, sound speed, and frequency-dependent acoustic attenuation spectra of ex vivo prostate tissue [39]. The dynamics of histotripsy bubble clouds can be significantly altered by the medium stiffness [37], [40. The concentration of agar was adjusted so that the elastic modulus of the phantom was 44 ± 0.4 kPa [41], similar to that observed in benign prostatic hyperplasia [42]–[44].…”
Section: Methodsmentioning
confidence: 99%